The effects of 2-hydroxyglutarate on the tumorigenesis of gliomas - Reiter-Brennan, Cara; Semmler, Lukas; Klein, Andreas (Contemporary Oncology/Współczesna Onkologia, 2018)
Mutation of the isocitrate-dehydrogenase (IDH) enzymes is one of the central research topics regarding gliomagenesis. Indeed, 70% of gliomas are associated with a gain-of-function IDH mutation and consequently synthesize the oncometabolite, 2-hydroxyglutarate (2-HG). This review aims to elucidate the effects of 2-HG on gliomagenesis. 2-HG promotes tumorigenesis by impacting metabolism, vascularization and altering the epigenome of glioma cells. Glioma metabolism and vascularization is altered by 2-HG’s effect on the stability of hypoxia-inducible factor (HIF) and inhibition of endostatin. However, 2-HG’s impacts on epigenetic mechanisms are more profound to gliomagenesis. Through competitive inhibition of JHDMs and TET proteins, 2-HG orchestrates histone and DNA hypermethylation, which is associated with gene silencing and dedifferentiation of cells. The hypermethylator phenotype induced by 2-HG also results in alterations of the interaction of the immune system with the tumour. Additionally, this study reviews 2-HG promotion of tumorigenesis by inhibiting repair of DNA alkylation damage through competitive inhibition of AlkB proteins.